Case Report: Anaphylactic shock and ST-elevation myocardial infarction following a bee sting: two deadly diseases in a patient with Kounis syndrome - Del Monaco, Guido; Pascucci, Carolina; Catapano, Federica; Stefanini, Giulio G.; Ferrante, Giuseppe (Frontiers in Cardiovascular Medicine, 2025)
Kounis syndrome is an acute coronary syndrome occurring in the setting of an allergic reaction, usually caused by drug administration, food ingestion, or insect sting. We report the case of an elderly woman who presented to the emergency room suffering from an anaphylactic shock caused by a bee sting and who was diagnosed with an anterolateral ST-elevation myocardial infarction (STEMI) with moderately impaired left ventricular ejection. The patient was successfully managed with the administration of intravenous antihistaminic drugs and steroids, intravenous fluid volume resuscitation, and intramuscular epinephrine. The patient then underwent emergency coronary angiography, which showed a thrombotic subtotal occlusion of the proximal left anterior descending artery (LAD) and occlusion of the very distal apical LAD due to a spontaneous embolism. This was treated by primary percutaneous coronary intervention with thrombus aspiration and drug-eluting stent implantation in the proximal LAD, achieving a good angiographic result. Nevertheless, on day 3, the patient developed a left ventricular apical thrombosis, as assessed by cardiac magnetic resonance, requiring oral anticoagulation with rivaroxaban, de-escalation of dual antiplatelet therapy from ticagrelor to clopidogrel with acetylsalicylic acid, and finally a switch to dual antithrombotic therapy. The 3-month follow-up was uneventful. This case highlights the importance of prompt identification of Kounis syndrome in patients presenting with severe allergic reactions to allow for the timely implementation of appropriate reperfusion strategies in such high-risk patients with STEMI.